O razlagi sodnih precedensov in sodb ter posebej sodb Evropskega sodišča za človekove pravice - Zupančič, Boštjan M. (Revus (Ljubljana), 2004)
In principle, judgment is not something that would need, or even should need to be interpreted. A concrete inter partes judgment itself must interpret the abstract legal norm. However, if it were true that judgments of the European Court of Human Rights had the strictly inter partes effect (as stated in Article 46 of the European Convention), there would be no need to interpret their abstract erga omnes effect. For the constitutional courts and other courts of last instance the reasoning based on syllogistic logic (logical subsumption of concrete facts under an abstract norm), which Continental lawyers are accustomed to, turns out to be almost completely useless, because in these instances the judges must often deal with the subsumption of concrete facts under the most abstract norm. The case-law of the European Court testifies to the need to fill in the enormous gap between an abstract meaning of a norm of the Convention and the facts of a concrete case. Half a century ago the Court was faced with this open space; it filled in the intermediate layers of case-law. The real substance of the Convention now lies in this casuistic jurisprudence. This then generates the need for interpretation of the Court's case-law - rather than the abstract provisions of the Convention itself. In principle, although the precedents of the European Court are only de facto binding on the State signatory of the Convention, the first instance courts and all courts of appeal ought to apply the Convention (as interpreted by the European Court). One, however, realizes that this is necessarily a long term assimilation process - also due to the language and other cultural communication barriers.
Keywords: človekove pravice; Evropsko sodišče za človekove pravice; pravna razlaga; sodbe; sodna praksa; sodni precedens